Numerical simulation of the compression crushing energy of carbon fiber-epoxy woven composite structures. (1st January 2023) - Rondina, Francesco; Falaschetti, Maria Pia; Zavatta, Nicola; Donati, Lorenzo
Abstract: The crashworthiness of composites is investigated in an experimental campaign and simulated using the explicit Finite Element solver ESI-VPS. Two damage models, derived from Ladevèze and Waas-Pineda, are implemented in modified forms, to work with woven-fabrics. The former uses conventional continuum damage formulations, while the latter introduces a traction-separation law to simulate cracks with prescribed fracture energies. The Waas-Pineda approach aims to simplify the material card definition and make the calibration more straightforward. Characterization tests are carried out on specimens manufactured with plain weave carbon fiber-epoxy tape. Notched coupons are analysed, as these tests are representative of the conditions observed during crushing of a composite structure. Innovative procedures to calibrate the damage models are introduced to remove, where possible, the need for iterative tuning. Once implemented, the calibrated material cards are validated against quasi-static crushing of corrugated specimens with two different layups. In the Waas-Pineda model, mesh objectivity is obtained only after correction of the modal fracture energies, instead, the Ladevèze model formulation is already consistent at different scale lengths. In addition, a sensitivity analysis shows a modest influence of friction coefficient and interlaminar fracture toughness on sustained load. Results demonstrate that it is possible to obtain adequate results from both damage models when the proposed calibration strategy is used, but validation on test results is still advised to ensure the mesh discretization is suitable for the selected problems.